2018
DOI: 10.1002/ajh.25059
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of anticoagulants for the treatment of venous thromboembolism in patients with cancer

Abstract: Anticoagulation is used to treat venous thromboembolism (VTE) in cancer patients, but may be associated with an increased risk of bleeding. VTE recurrence and major bleeding were assessed in cancer patients treated for VTE with the most currently prescribed anticoagulants in clinical practice. Newly diagnosed cancer patients (first VTE 1/1/2013‐05/31/2015) who initiated rivaroxaban, low‐molecular‐weight heparin (LMWH), or warfarin were identified from Humana claims data and observed until end of eligibility or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 27 publications
6
69
1
Order By: Relevance
“…For instance, a single‐institution cohort study limiting rivaroxaban use to patients without active gastrointestinal tract or urinary tract lesions and performing empirical dose reduction in elderly patients has reported rates of major bleeding and recurrent VTE of 2.2% (95% CI 0–4.2%) and 4.4% (95% CI 1.4–7.4%), respectively . Similarly, in a large US claims dataset of 2428 patients, there were lower rates of recurrent VTE in rivaroxaban users than in LMWH users at 6 months (13.2% versus 17.1%; P = 0.06) and 12 months (16.5% versus 22.2%; P = 0.03) (HR 0.72, 95% CI, 0.52–0.95; P = 0.02), without any differences in major bleeding . A recently published systematic review of the literature describing all observational studies on this topic reported that most studies used rivaroxaban and enoxaparin .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a single‐institution cohort study limiting rivaroxaban use to patients without active gastrointestinal tract or urinary tract lesions and performing empirical dose reduction in elderly patients has reported rates of major bleeding and recurrent VTE of 2.2% (95% CI 0–4.2%) and 4.4% (95% CI 1.4–7.4%), respectively . Similarly, in a large US claims dataset of 2428 patients, there were lower rates of recurrent VTE in rivaroxaban users than in LMWH users at 6 months (13.2% versus 17.1%; P = 0.06) and 12 months (16.5% versus 22.2%; P = 0.03) (HR 0.72, 95% CI, 0.52–0.95; P = 0.02), without any differences in major bleeding . A recently published systematic review of the literature describing all observational studies on this topic reported that most studies used rivaroxaban and enoxaparin .…”
Section: Introductionmentioning
confidence: 99%
“…Several subanalyses and meta‐analyses of data from RCTs have found similar efficacy and safety outcomes with DOACs and VKAs or standard therapy in patients with cancer (Table ). In a large‐scale meta‐analysis, Brunetti et al compared the efficacy and safety of DOACs with those of conventional treatment with either a VKA (seven trials) or LMWH (two trials) in 1,952 patients with VTE and cancer .…”
Section: Doacs In Patients With Vte or Af And Cancermentioning
confidence: 99%
“…When DOACs were compared with VKAs and LMWHs separately, DOACs were associated with higher rates of bleeding than LMWHs but were found to be as effective as and to have a similar safety profile to VKAs . Data from retrospective or observational studies in patients with cancer and VTE seem to indicate that DOACs have a similar efficacy and tolerability profile (including the risk of major bleeding) to LMWHs (Table ) . The vast majority of these clinical data was collected when specific reversal agents for the DOACs were not available.…”
Section: Doacs In Patients With Vte or Af And Cancermentioning
confidence: 99%
“…Recently, a real‐world study of primarily Medicare‐insured patients compared the risk of recurrent venous thromboembolism (VTE) and major bleeding associated with rivaroxaban, warfarin, and low‐molecular weight heparin (LMWH) following a first‐episode of VTE among patients with cancer . Results suggested that rivaroxaban treatment is associated with a lower risk of recurrent VTE versus LMWH or warfarin, and that the rate of major bleeding does not significantly differ across treatments .…”
Section: Patient Characteristics Of Weighted Cohortsmentioning
confidence: 99%